Wish [videorecording (Blu-Ray + DVD)] - Buck, Chris; Veerasunthorn, Fawn; Lee, Jennifer (Screenwriter); Moore, Allison Lee (Disney, 2024)
Asha, a sharp-witted idealist, makes a wish so powerful that it is answered by a cosmic force, a little ball of boundless energy called Star. Together, Asha and Star confront a most formidable foe the ruler of Rosas, King Magnifico to save her community and prove that when the will of one courageous human connects with the magic of the stars, wondrous things can happen.